2016
DOI: 10.1016/j.metabol.2016.04.001
|View full text |Cite
|
Sign up to set email alerts
|

Catechol-O-methyltransferase association with hemoglobin A1c

Abstract: Aims Catecholamines have metabolic effects on blood pressure, insulin sensitivity and blood glucose. Genetic variation in catechol-O-methyltransferase (COMT), an enzyme that degrades catecholamines, is associated with cardiometabolic risk factors and incident cardiovascular disease (CVD). Here we examined COMT effects on glycemic function and type 2 diabetes. Methods We tested whether COMT polymorphisms were associated with baseline HbA1c in the Women’s Genome Health Study (WGHS), and Meta-Analyses of Glucos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
13
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 27 publications
(41 reference statements)
1
13
0
Order By: Relevance
“…They achieved significantly better HbA1c values after the 52-week treatment compared to patients carrying the GG genotype, pointing to the fact that presence of one or two A allele of the COMT Val108/158Met could be associated with a better response to insulin detemir therapy. This finding differs from the data from a recent study that reported an association of the G allele with lower values of HbA1c [ 50 ], but is partly consistent with the results from a male obesity study in Denmark in which the GG genotype was associated with impaired glucose tolerance and high fat BMI [ 29 , 50 ].…”
Section: Discussionsupporting
confidence: 56%
“…They achieved significantly better HbA1c values after the 52-week treatment compared to patients carrying the GG genotype, pointing to the fact that presence of one or two A allele of the COMT Val108/158Met could be associated with a better response to insulin detemir therapy. This finding differs from the data from a recent study that reported an association of the G allele with lower values of HbA1c [ 50 ], but is partly consistent with the results from a male obesity study in Denmark in which the GG genotype was associated with impaired glucose tolerance and high fat BMI [ 29 , 50 ].…”
Section: Discussionsupporting
confidence: 56%
“…The COMT val-allele was modestly protective from risk of Type II diabetes [ [50][51] Cardiovascular disease The val-allele was protective from risk of cardiovascular disease in several studies [48,52,53] † The COMT rs4680 val-allele encodes a form of the enzyme which is 3-4× more active than the met-allele form.…”
Section: Diabetesmentioning
confidence: 99%
“…Experimental and clinical data link reduced COMT activity and 2ME levels to the development of obesity and insulin resistance [99,100]. Moreover, a low-activity variant of COMT (val/met 158) may contribute to MS [99], whereas the high-activity form of COMT (rs4680) is associated with lower HbA1c and protection from type 2 diabetes [101]. Also, both genetic and pharmacologically-induced deficiency of COMT exacerbates high-fat diet (HFD)-induced insulin resistance in mice [100].…”
Section: Other Effects Of the 2-methylation Pathway Relevant To Pahmentioning
confidence: 99%